Clinical Outcomes of Cholangioscopy as a Minimally Invasive Intervention for Common Bile Duct Stones - Putri, Septy Rianty Salsabilla Dwi; Wahyudi, Reza Rizwandipa; Prameswari, Devi Shanti; Dwiandika, Rizky Ary; Tahriani, Ridha; Salsabila, Ruhania Najwa; Sena, Cantika Brilian; Jibriel, Diaz Azhalea; Budyono, Catarina (The Indonesian Society for Digestive Endoscopy, 2025)
Choledocholithiasis is a condition of obstruction in the bile duct due to stones, which is classified into primary and secondary. Primary choledocholithiasis occurs due to obstruction of bile flow that triggers stone formation, while the secondary form is caused by gallstones that have formed previously and moved to the common bile duct, causing obstruction. This condition can cause various serious complications that require different treatments. This article discusses the role of cholangioscopy as a minimally invasive intervention in the diagnosis and therapy of choledocholithiasis. The results of the study showed that cholangioscopy plays an important role in endoscopic therapy and lithotripsy. However, the availability of cholangioscopy equipment in Indonesia is still limited, so its current use is more as a supporting procedure for Endoscopic Retrograde Cholangiopancreatography (ERCP). The purpose of this study was to evaluate the clinical effectiveness of cholangioscopy in the treatment of choledocholithiasis, especially in complex cases that are difficult to treat with conventional methods.